Empowering Society for Better Corporate Social Responsibility (CSR): The Case of Malaysia - Azlan Amran; Mustaffa Mohamed Zain; Maliah Sulaiman; Tapan Sarker; Say Keat Ooi (Kajian Malaysia, 2013)
This article presents a theoretical proposition based on stakeholder theory for better Corporate Social Responsibility (CSR) practices, specifically in the context of Malaysia. The aim of this article is to argue the need for a government initiative to help empower local communities and transform them into legitimate and powerful stakeholders. An understanding of the concept and importance of CSR is still lacking among the local communities in Malaysia, in contrast to the communities in certain developed nations where the idea of CSR originated. Competing for the limited resources of the firm, communities need to understand that they also have a role in promoting better CSR. This article contributes to the literature by providing a fundamental explanation of how the community could be empowered to become an important driver of CSR practices, contributing to a better atmosphere if both firms and communities work together towards a sustainable livelihood. The public sector includes all types of government agencies, which should play their role in providing awareness to the community about its rights and capability to become an effective change agent regarding the responsibility of firms operating within its environment.